Effectiveness of TVET in Nepal - Adhikari, Ramesh; Adhikari, Shiva Raj; Upreti, Dilli Ram; Adhikari, Keshav Prasad (Journal of Technical and Vocational Education and Training, 2023)
The technical and vocational education and training (TVET) program has been implemented in the country for a long time. Nevertheless, the actual impact it had made on the national economy is unknown. The main objective of this study is to examine the effectiveness of the TVET program in Nepal. The study employed concurrent mixed methods which used both quantitative and qualitative approaches. A retrospective post-then-pre design was used in this study. A total of 21 districts (3 districts from each province) were selected. A survey was conducted with 1,231 Diploma and Pre-Diploma (TSLC) graduates who studied in the institutions either affiliated to or constituent of the Council for Technical Education and Vocational Training (CTEVT). Similarly, 42 key informants’ interviews (2 from each district) were conducted with key stakeholders, such as school principals, instructors, and employers. Overall, out of the total graduates, only 8.8% were working before joining TVET, and the remaining 91% did not work, while the percentage of graduates employed during the time of survey was 58.2%. A remarkable difference in average income was found before and after graduation (NRs 1,815 vs NRs 15,656). The income difference was highest among the people who studied engineering (NRs 16,005) followed by health (NRs 14,908). The income of males was 1.6 times higher than that of females after graduation. Current income is higher among graduates from Lumbini Province (NRs 21,427), followed by Province-1 (NRs 20,396). The study revealed that overall, TVET has a positive impact on the society's economy through increased employment opportunities among youths. TVET has been effective in generating employment for many young people, ultimately contributing to elevate the family's economic status, thereby ensuring quality life.